IMPLEMENTASI KELUARGA SAKINAH BERKEMAJUAN TERHADAP FENOMENA FATHERLESS - Maulidi Dhuha Yaum Mubarok (Universitas Nurul Jadid, 2023)
This paper focuses on discussing how the implementation of a progressive Sakinah family is a provision to face family challenges in this global era, especially the fatherless phenomenon. The data for this research comes from reading the results of previous research relating to fatherless which is adapted to the latest developments and uses a sociological normative approach with a deductive-inductive thinking model. Fatherless as a social phenomenon in Indonesia is the impact of the massive development of the times which demands adaptation from each individual. Fatherless is a condition where the presence of a father is absent both physically and psychologically which has an impact on the family institution. Another reason for this phenomenon is the shift from the patriarchal family system to a democratic family system, where all family members have the same roles, functions, and opportunities to actualize themselves both in the domestic (home) and public spheres. The results of the study show that the Sakinah family is an ideal portrait of a family building that each individual must strive to make as much effort as possible to make happen. Progressive Sakinah families are able to fulfill the rights of other family members, armed with communication patterns that respect and understand each other, as a result of individuals who are pious and have the nature of mercy.